The Role of Creative Thinking in Enhancing Self-Actualization Among Female University Students: A Field Study on Female Students at the Faculty of Education, Abu Issa, University of Zawiya (Comprehensive Journal of Science, 2026)
This study aimed to identify the level of creative thinking and self-actualization among female students at Abu Issa Faculty of Education, University of Zawia, examine the relationship between them, and determine the effect of creative thinking on self-actualization, The study adopted the descriptive-analytical method and was conducted on a sample of 138 female students using a questionnaire, The results showed that both creative thinking and self-actualization were at a moderate level, They also revealed a statistically significant positive relationship between the two variables and a significant effect of creative thinking on self-actualization.
Keywords: Creative thinking, Self-actualization, Female university students, Abu Issa Faculty of Education, University of Zawia